2021
DOI: 10.1152/ajpheart.00065.2021
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α-activated eNOS signaling increases leukocyte adhesion through the S-nitrosylation pathway

Abstract: Nitric oxide (NO) is a key factor in inflammation produced by endothelial nitric oxide synthase (eNOS) in endothelium, whose activity increases after stimulation with pro-inflammatory cytokines. NO activates the soluble guanylate cyclase-protein kinase G and S-nitrosylation (NO modification of free-thiol cysteines in proteins) pathways. NO is classically described as a negative regulator of leukocyte adhesion to endothelial cells. However, agonists activating NO production induce fast leukocyte adhesion sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Our results showing NO as a signal that promotes cell adhesion to the endothelium are in strong contrast to studies showing an inhibitory role of NO in this process [ 16 , 24 , 38 , 73 ]. Besides the differences in the cell and animal models used, we propose that these discrepancies can be explained by the fact that the physiological effects of NO strictly depend on its concentration, duration of exposure, location, and activity of NOS isoforms [ 2 , 3 ]. In non-stimulated cells, basal NO production could maintain an anti-adhesive phenotype [ 23 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showing NO as a signal that promotes cell adhesion to the endothelium are in strong contrast to studies showing an inhibitory role of NO in this process [ 16 , 24 , 38 , 73 ]. Besides the differences in the cell and animal models used, we propose that these discrepancies can be explained by the fact that the physiological effects of NO strictly depend on its concentration, duration of exposure, location, and activity of NOS isoforms [ 2 , 3 ]. In non-stimulated cells, basal NO production could maintain an anti-adhesive phenotype [ 23 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…We use a modification of the protocol previously described by us [ 2 ]. Briefly, confluent EAHy926 cells were loaded with DAF-FM Diacetate (5 mM, Invitrogen, Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Since NO is classically described as a negative regulator of leukocyte adhesion, upregulation of ICAM-1 and increased U937 recruitment on HMEC-1 cells was a quite unexpected result. However, a recent study by Aguilar et al demonstrated that TNF-α-activated eNOS signaling can increase leukocyte adhesion through ICAM-1 and the S-nitrosylation pathway [ 47 , 48 , 49 ]. In line with these data, our findings also demonstrated that overproduction of NO plays a key role in U937 cellular adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of connexin contribution to the hyperpermeability response, inasmuch as agonist-induced eNOS translocation from the plasma membrane to cytosol and subsequent cytosolic NO production is crucial to agonist-induced hyperpermeability [126,[201][202][203][204][205], influencing S-nitrosylation and the disassembly of AJs proteins and VASP [206][207][208][209][210][211][212][213]. The participation of GJ channels or Cxs-hemichannels in hyperpermeability may be related to a NO-cGMP-PKG pathway.…”
Section: Connexin Proteins In Postcapillary Venules Hyperpermeabilitymentioning
confidence: 99%